An anion exchange strategy for construction of a novel Bi2SiO5/Bi2MoO6 heterostructure with enhanced photocatalytic performance. Issue 13 (12th June 2018) - Liu, Di; Wang, Jun; Wang, Yonggang; Zhu, Yongfa
Abstract : A novel Bi2 SiO5 /Bi2 MoO6 heterojunction with a highly efficient photocatalytic performance was successfully designed and constructed via an anion exchange strategy. Abstract : Based on the structural similarity and the driving principle of solubility, we successfully constructed heterostructures of Bi2 SiO5 /Bi2 MoO6 through an anion exchange strategy between Bi2 MoO6 starting material and incoming SiO3 2− ions. By tuning the addition amount of incoming SiO3 2−, the evolution process of the Bi2 SiO5 /Bi2 MoO6 heterostructures involving phase formation, morphology transformation, and changes in specific surface area and optical properties was clearly identified. More importantly, the heterostructured products displayed remarkably enhanced photodegradation activities under UV and visible light irradiation compared to pure Bi2 MoO6, which could be mainly ascribed to the relatively high surface areas, the light-harvesting contribution from the Bi2 MoO6 component, and effective separation of photo-generated electron—hole pairs driven by the interfacial potential difference in the Bi2 SiO5 /Bi2 MoO6 heterojunctions.